2018
DOI: 10.1093/heapro/day114
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and implementing a health promoting school in rural Cambodia

Abstract: Summary Few studies have used a whole-of-school approach in implementing a health promoting schools (HPS) framework. Descriptions of how HPS is being implemented, particularly in low-resourced, developing countries, are limited. This study used an exploratory case study design to examine the planning and implementation of a HPS in a rural Cambodian village. Data were collected via observations of the school, school documentation, and interviews with stakeholders (n = 9). The data were analysed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…1,9,17 Cambodia also depends on overseas aid to pursue educational development and a range of funded projects targeted at resolving key educational issues. 18,19 As Cambodia's newly endorsed national policy focuses on general physical health, 8,20,21 we can observe some similarities with Japan. However, while its national policy does not explicitly reference HPS, many aspects of the approach are present.…”
Section: Discussionmentioning
confidence: 95%
“…1,9,17 Cambodia also depends on overseas aid to pursue educational development and a range of funded projects targeted at resolving key educational issues. 18,19 As Cambodia's newly endorsed national policy focuses on general physical health, 8,20,21 we can observe some similarities with Japan. However, while its national policy does not explicitly reference HPS, many aspects of the approach are present.…”
Section: Discussionmentioning
confidence: 95%
“…Also, few studies have evaluated the degree of implementation of health promotion programs in HPS, and their results are inconclusive ( Ramos et al, 2013 ). Furthermore, previous studies have identified barriers for the implementation of health programs in the school context, namely the lack of engagement and understanding of the students, their families and the local community ( Ramos et al, 2013 ; Clelland, Cushman & Hawkins, 2013 ), problems with the coordination ( Ramos et al, 2013 ) and management ( Heesch et al, 2020 ) of these programs, unclear roles and responsibilities of the agents involved ( Silva et al, 2019 ; Ramos et al, 2013 ; Mannix-Mcnamara et al, 2012 ), and lack of human, material and economic resources ( Silva et al, 2019 ; Ramos et al, 2013 ; Heesch et al, 2020 ). Other barriers stem from the low level of implication of the teachers ( Jourdan et al, 2011 ), their low self-efficacy to influence the students’ behavior ( Clelland, Cushman & Hawkins, 2013 ), a difficulty to personally relate to the health promotion program’s aims and objectives ( Ramos et al, 2013 ) and not considering school health as a priority ( Saito et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers stem from the low level of implication of the teachers ( Jourdan et al, 2011 ), their low self-efficacy to influence the students’ behavior ( Clelland, Cushman & Hawkins, 2013 ), a difficulty to personally relate to the health promotion program’s aims and objectives ( Ramos et al, 2013 ) and not considering school health as a priority ( Saito et al, 2015 ). Similarly, there are factors that facilitate the implementation of health programs in HPS, including: (1) continuing education and training courses, and support, for teachers implementing health programs ( Moynihan, Jourdan & Mannix McNamara, 2016 ; Silva et al, 2019 ; Ramos et al, 2013 ; Jourdan et al, 2011 ); (2) higher engagement and implication of the school community ( Silva et al, 2019 ; Ramos et al, 2013 ); (3) higher level of sustainability and impact of interventions ( Passmore & Donovan, 2014 ); (4) intersectoral collaboration and liaison with the local community ( Heesch et al, 2020 ; Tooher et al, 2017 ; Hung et al, 2014 ); (5) promotion of a culture of change and active participation ( Heesch et al, 2020 ; Hung et al, 2014 ); (6) dissemination of HPS programs amongst schools, organizations and the general population ( Silva et al, 2019 ); (7) integrative and holistic approaches designed, managed and implemented systematically ( Ramos et al, 2013 ; Heesch et al, 2020 ; Lee & Cheung, 2017 ; Samdal & Rowling, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HPS model has shaped school health promotion in different parts of the world including the low-income countries [18]. The WHO Global Accelerated Action for the Health of Adolescents (AA-HA!)…”
Section: Healthy School Award Scheme To Establish High Quality Standamentioning
confidence: 99%
“…Therefore, updating of HPS through scoping study is needed to identify the indicators of HPS to highlight the ways in which schools have adopted HPS principles successfully under the six key areas: healthy school policies, school physical environment, school social environment, action competencies for healthy living, school health care and promotion services, and community link [12,13], and the conditions to be in place to flourish. There is also a need to review the evidence of HPS effectiveness on a boarder perspective dealing with complexity of the school system [31] to link education and health [18,32]. The following sections report the findings from international forums, review of recent literature, documents and guidelines from international institutions on HPS and child and adolescent health to supplement and substantiate the core indicators and requirements evolved from HKHSA, an established award-scheme framework.…”
Section: Healthy School Award Scheme To Establish High Quality Standamentioning
confidence: 99%